Monitoring of atmospheric emission of alpha emitters radionuclides at a nuclear fuel cycle facility in RJ, Brazil - Wagner De Souza Pereira; José Marques Lopes; Alessander sá Do Carmo; Emanuele L. C. Campelo; Alphonse Kelecoml; Ademir Xavier Da Silva (Brazilian Journal of Radiation Sciences, 2021)
The Indústrias Nucleares do Brasil S/A (INB) in Resende, state of Rio de Janeiro, operate with open sources containing alpha emitters. This operation produces particulate material in the air. To reduce this impact, the plant operates with negative pressure using an exhaust equipment. Exhaust air is sent to an absolute filter system. In the exhaust stack, there is an alpha emitter detection module that operates monitoring the releases. Following the dose calculation model established by the National Commission for Nuclear Energy (CNEN), the authorized limit is fixed at 1.2∙107 Bq.y-1 of alpha emitters by Nuclear Fuel Factory (FCN). The present work aims to evaluate the alpha-emitting radionuclides released by FCN in terms of total release (Bq) and activity concentration (AC, Bq∙m-3). In 2018, FCN released 1.41∙106 Bq.y-1(i.e. 34% of the 2016 releases). The largest mean for AC was 2.04 mBq∙m-3. The release data was almost an order of magnitude lower than the annual release limit, proving the adequation of the atmospheric effluents to the licensing requirements.